2015
DOI: 10.1007/s12070-015-0824-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Transient Evoked Otoacoustic Emissions (TEOAEs) and Distortion Products Otoacoustic Emissions (DPOAEs) in Normal Hearing Subjects With and Without Tinnitus

Abstract: The aim of this study was to investigate the possible role of cochlear outer hair cell function with TEOAE and DPOAE tests in patients with normal hearing and tinnitus. 25 tinnitus patients with normal hearing sensitivity selected as study group. Control group consist of 50 normal hearing subjects without tinnitus. All subjects had thresholds below 25 dBHL at frequencies 250-8,000 Hz, tympanogram type A and normal acoustic reflex thresholds. TEOAE were recorded with click stimulus at 80 dB SPL at 1,000, 2,000,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…24 Cochlear affection is supported by the significant elevation of hearing threshold at all frequencies including the extended high frequencies, and the significant reduction of TEOAE amplitude in tinnitus patients, as evidenced in the current study and in literature. 8,16,25 Otoacoustic emissions originate from properly functioning outer hair cells. Thus, the presence of cochlear dysfunction will cause reduction or even absence of the otoacoustic emissions.…”
mentioning
confidence: 99%
“…24 Cochlear affection is supported by the significant elevation of hearing threshold at all frequencies including the extended high frequencies, and the significant reduction of TEOAE amplitude in tinnitus patients, as evidenced in the current study and in literature. 8,16,25 Otoacoustic emissions originate from properly functioning outer hair cells. Thus, the presence of cochlear dysfunction will cause reduction or even absence of the otoacoustic emissions.…”
mentioning
confidence: 99%
“…In addition, due to the evaluation of the larger frequency spectrum, it is possible to examine the cochlear function from the basal (high frequencies) to the apical (low frequencies) [10]. There are several studies on DPOAE in people with tinnitus and normal hearing that have been performed in different ways such as pass/refer rates [11], normal/abnormal rates [12], DPOAE alteration [13,14], the slope of input/output function [15] and DPOAE amplitude in the frequency range of 1−8 kHz [16,17]. Past studies have reported significant differences in DPOAE parameters between patients with and without tinnitus when adjusted for their hearing thresholds up to 8 kHz [3,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that have tried to correlate the sound levels of distortion products with tinnitus characteristics. The results are very inhomogeneous and describe almost every possible scenario like no difference at all 83,84 , lower DP amplitudes in tinnitus patients 85,86,84,87 , hinting towards OHC dysfunction as a possible cause for tinnitus 88,89 or higher DP amplitudes in tinnitus patients theorized to be because of higher motility of the OHC´s 90,91 . In alignment with most studies describing "normal-hearing" the distinction was made using clinical audiometry without including frequencies above 8 kHz thus suffering the same inaccuracies as described in chapter 4.2., and thereby explaining the inhomogeneous results.…”
Section: Links Between Synaptopathy and Tinnitusmentioning
confidence: 90%